Clinicotopographical correlation of corticospinal tract stroke: a color-coded diffusion tensor imaging study - Na, Chuh-Hyoun; Hirsch, J. G.; Rossmanith, C.; Hennerici, Michael G.; Gass, Achim (Stroke, 2004)
Background- Small capsular strokes are difficult to assess with regard to the precise location and the extent of pyramidal tract damage with conventional brain imaging. Color-coded diffusion tensor imaging (CDTI) provides a means to visualize the course of the corticospinal tract within the white matter. In addition to T2-weighted MRI, diffusion-weighted MRI and CDTI were used to analyze the topographical patterns of small lacunar corticospinal tract strokes. - METHODS: We examined 15 patients with pyramidal tract strokes in the subacute phase (days 3 to 7). Lesions were identified on diffusion-weighted MRI and superimposed on CDTI images. The anatomic location and pattern of the lesion were visualized on CDTI with regard to the corticospinal tract and subsequently compared with the clinical presentation. In addition, infarct areas were evaluated with quantitative parameters: mean diffusivity and lattice anisotropy index of lesions were determined. - RESULTS: We identified 5 different patterns of corticospinal tract stroke falling into 2 clinical subgroups: (1) those with marked deficits and minor improvement (6/15) and (2) those with good recovery (9/15). Group 1 had long lesions centered in the pyramidal tract, involving the basal ganglia (anterior choroidal artery); group 2 lesions were very small and/or located anteriorly and medially (periventricular anterior choroidal artery territory; thalamogeniculate, tuberothalamic, and lateral striate branches). Lesions showed a significant increase of mean diffusivity and decrease of lattice anisotropy. - CONCLUSIONS: CDTI allows in vivo differentiation of distinct subcortical stroke subtypes. Improved anatomic definition of lesion localization using CDTI may help in better establishing the prognosis for patients after subcortical stroke.